2022
DOI: 10.1039/d2nr02892a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of functional layers thinning of high temperature polymer electrolyte membrane fuel cells after long term operation

Abstract: The operation related degradation processes of high temperature polymer electrolyte membrane fuel cell after long term operation (12 000 h) with hydrogen-rich reformate gas are studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Besides the previously mentioned degradation mechanisms, in bimetallic systems, other phenomena can occur. For instance, in bimetallic Pt–Ru particles preferential dissolution of Ru can take place . Even in core–shell NPs, Ru-core dissolution can take place if the Pt-shell is not fully covering the core or by thermally induced shape fluctuations of the shell, both of which result in the less stable core metal being exposed to the electrolyte, with its consequent dissolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the previously mentioned degradation mechanisms, in bimetallic systems, other phenomena can occur. For instance, in bimetallic Pt–Ru particles preferential dissolution of Ru can take place . Even in core–shell NPs, Ru-core dissolution can take place if the Pt-shell is not fully covering the core or by thermally induced shape fluctuations of the shell, both of which result in the less stable core metal being exposed to the electrolyte, with its consequent dissolution.…”
Section: Resultsmentioning
confidence: 99%
“…Particle dissolution, agglomeration, Ostwald ripening, and particle detachment have been reported as some of the main phenomena affecting state-of-the-art Pt-based PEMFC catalysts . Moreover, when Pt is alloyed with a less stable transition metal, such as Ni or Co, the preferential dissolution of these metals can take place. , This process also affects Pt–Ru-based catalysts, the materials of choice for CO-tolerant PEMFC anodes due to their superior catalytic activity, , which impacts greatly their performance toward the HOR. Therefore, it is still necessary to find a durable anode catalyst that can boost the commercial viability of PEMFCs .…”
mentioning
confidence: 99%
“…[45,256] Additionally, ECSA decreases due to the operation-specific harsh conditions in HT-PEMFC. Recently, Vega Paredes et al [257] studied long-term operation degradation (12 000 h) at 0.2 A cm −2 and 160 °C, in a HT-PEMFC stack. They found two operation-related degradation mechanisms, (1) thinning of the functional layers as well as Kerr et al, [249] and (2) dissolved catalyst redistribution within the MEA.…”
Section: Catalyst Degradationmentioning
confidence: 99%
“…The primary reason behind nanostructuring the catalyst into core-shell NPs, is to protect the less stable Ru, since it is well known that surface Ru can dissolve under operating conditions [35]. In fact, previous studies have shown that when solid solution [36,39] or bimetallic [13] Pt-Ru NPs are used as anode catalyst, Ru crosses over from the anode towards the cathode trough the membrane. On the other hand, Hsieh et al [17] demonstrated a superior stability of well-ordered Ru@Pt NPs during accelerated stress tests.…”
Section: Understanding the Degradation Of Ru@pt Catalystsmentioning
confidence: 99%